Pengaruh Kualitas Pelayanan, Kualitas Produk, Harga dan Rumah Makan Atmosphere Terhadap Kepuasan Konsumen Rumah Makan “Lempah Kuning Muara” di Kota Pangkalpinang - Valentiani, Valentiani; Muntoro, Muntoro; Evahelda, Evahelda (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
This study aims to analyze the effect of service quality, product quality, price, and restaurant atmosphere on customer satisfaction at “Lempah Kuning Muara” Restaurant in Pangkalpinang City. Data collection was carried out for three months from May to July 2025 at “Lempah Kuning Muara” Restaurant in Pangkalpinang City. The research method used is the survey method. The sampling method used is purposive sampling with a total sample of 110 respondents. Sample collection was conducted through observation, interviews, and questionnaires. Data analysis used descriptive analysis and SEM-PLS (Structural Equation Modeling-Partial Least Square) with SmartPLS Version 4.0 software. The results of the study showed that the variables of product quality, price, and restaurant atmosphere had a positive effect on customer satisfaction, while service quality had no effect on customer satisfaction at “Lempah Kuning Muara” Restaurant.